Mengembangkan Sikap Ilmiah Siswa dengan Model Pembelajaran Learning Cycle di SD Negeri Semawung - Antika Rizka Saputri; Wahdaniyah Sekar Rahma; Lilis Dita Prastiwi (Indonesian Journal of Elementary and Childhood Education, 2023)
This study aims to develop scientific attitudes in students with the 5-E Learning Cycle model. The research subjects were fifth grade students of SD Negeri Semawung. The method used is observation and simulation or class action assessment. The research instrument used is the result of observations and the results of learning simulations using the Learning Cycle method with material guidance in the Thematic Book of Class V Students Theme 7, especially in Sub-theme 1 Learning 2 where the materials are Indonesian, Natural Science, and SBdP. In this study, researchers used qualitative methods through interviews, observations, and interviews. After conducting a learning simulation using the Learning Cycle Model, there was an increase in the scientific attitude of students compared to using the previous model. Before using the Learning Cycle Model, the average scientific attitude was 75.15666667 including the sufficient category and after using the Learning Cycle Model it increased to 77.96, namely in the good category. So it can be seen that this model can improve the scientific attitude of students.